A Framework for implementing radiation-tolerant circuits on reconfigurable FPGAs - Manuel G. Gericota (2006)
The outstanding versatility of SRAM-based FPGAs make them the preferred choice for implementing complex customizable circuits. To increase the amount of logic available, manufacturers are using nanometric technologies to boost logic density and reduce prices. However, the use of nanometric scales also makes FPGAs particularly vulnerable to radiation-induced faults, especially because of the increasing amount of configuration memory cells that are necessary to define their functionality. This paper describes a framework for implementing circuits immune to radiation-induced faults, based on a customized Triple Modular Redundancy (TMR) infrastructure and on a detection-and-fix controller. This controller is responsible for the detection of data incoherencies, location of the faulty module and restoration of the original configuration, without affecting the normal operation of the mission logic. A short survey of the most recent data published concerning the impact of radiation-induced faults in FPGAs is presented to support the assumptions underlying our proposed framework. A detailed explanation of the controller functionality is also provided, followed by an experimental case study.